Comparison of ranibizumab versus dexamethasone for macular oedema following retinal vein occlusion: 1‐year results of the COMRADE extension study. Issue 8 (31st May 2018) - Feltgen, Nicolas; Hattenbach, Lars‐Olof; Bertelmann, Thomas; Callizo, Josep; Rehak, Matus; Wolf, Armin; Berk, Hüsnü; Eter, Nicole; Lang, Gabriele E.; Pielen, Amelie; Schmitz‐Valckenberg, Steffen; Quiering, Claudia; et al.
Abstract: Purpose: The COMRADE studies are the first randomized controlled head‐to‐head trials comparing the efficacy and safety of intravitreal ranibizumab versus dexamethasone (DEX) in patients with macular oedema secondary to retinal vein occlusion (RVO). The COMRADE extension trial was designed to provide additional 6‐month data of patients who completed the core studies. Methods: In this open‐label, phase IV study patients who completed the COMRADE core studies were prospectively enrolled. Overall, 92 branch RVO (BRVO) patients (ranibizumab 52, DEX 40) and 83 central RVO (CRVO) patients (ranibizumab 61, DEX 22) were treated, and 94.6% of BRVO patients and 97.6% of CRVO patients completed the extension study. Patients were assigned to the same treatment group as in the core studies. Patients were monitored monthly and received either 0.5 mg ranibizumab or a 0.7 mg DEX implant as needed. Results: Over the course of the extension, treatment‐emergent adverse events (TEAEs) of the study eye occurred in 55.8% of BRVO patients on ranibizumab and in 62.5% of those on DEX. Among CRVO patients, 65.5% in the ranibizumab group and 59.1% in the DEX group developed TEAEs. Overall, elevated intraocular pressure (IOP) was more frequent with DEX than ranibizumab treatment. Mean average change in best‐corrected visual acuity (BCVA) in BRVO patients was significantly better for ranibizumab than DEX (p = 0.0249). The CRVO results were consistent with BRVO's, although not significant (p = 0.1119). Conclusion: When used according to the European labels, ranibizumab revealed a better ocular safety profile and produced greater average BCVA gains than DEX. By the end of the additional 6‐month study period, this difference in BCVA was more pronounced in BRVO as in CRVO patients. The main limitation of the COMRADE studies was that DEX patients received only a single intravitreal treatment during the first 6 months, which is presumably not adequate. However, frequent DEX implants could lead to more steroid‐related side effects, especially to an increased intraocular pressure.